Infected area by major pests of paddy in MADA region / Siti Salbiah Mat Desa - Mat Desa, Siti Salbiah (Faculty of Plantation and Agrotechnology, 2017)
Pests are one of the major biotic constraints in rice production throughout the world. Pests potentially damaging plants by feeding of a plant part, chewing on plant tissues, boring into stems or sucking fluid sap from stem and grains. Their diverse invasions in paddy field and the capability of damaging various plant parts is a concern to farmers on their rice production. Brown planthopper (Nilaparvata lugens), white-backed planthopper (Sogatella fucifera), yellow stem borer (Scirpophaga incertulas), rice leaf roller (Cnaphalocrosis medinalis), green leafhopper (Nephotettix viresens), and thrips (Stenchaetothrips biformis) are listed as the insect pests of paddy. Meanwhile, golden apple snail (Pomacea canaliculata) and rice field rat (Rattus argentiventer) are gastropod and vertebrate pests also deliberated as destructive pests in a rice field. The aims of these studies are to determine the total infected area by major pests of paddy in MADA regions as well as identifying the highest infected area by the pests between the regions. Secondary data on pests invasions were collected in two plant-ing seasons starting from April 2015 to September 2015 (Season 1/2015) and October 2015 to April 2016 (Season 2/2015) from MADA. Outcomes of the study show the highest infected area (17.30%) by rice leaf roller (Cnaphalocrosis medinalis) in Season 1 for Region 2 (Jitra). Meanwhile, for Season 2, the highest infected areas (12.34%) by golden apple snail (Pomacea canaliculata) also reported for Region 2 (Jitra). Concisely, golden apple snail (Pomacea canaliculata) remains as the major rice pest in all regions with its persistency is recorded in both seasons at MADA regions. Close monitoring and control management should be focused at Region 2 (Jitra) with emphasized on golden apple snail attacks.